Matching NPWP and NIK in the Perspective of Indonesian Tax Law: A Comprehensive Study of the Principles of Legal Certainty and Justice for Taxpayers - Evansarid, Argi; Albab, Ulil; Amiludin, Amiludin (Universitas Muhammadiyah Sumatera Utara, 2025)
The policy of matching the Taxpayer Identification Number (TIN) with the National Identity Number (NIN) in Indonesia is implemented to enhance the efficiency of tax administration and the accuracy of taxpayer identification. Although the objectives of this policy are positive, its implementation faces several legal challenges, particularly related to the principles of legal certainty and fairness for taxpayers. This study aims to comprehensively evaluate the policy from the perspective of Indonesian tax law. The research employs a qualitative approach combining normative and empirical legal research methods. Normative research was conducted through the analysis of tax regulations, while empirical research involved data collection through interviews with tax practitioners, officials from the Directorate General of Taxes, and relevant taxpayers. The findings reveal that this policy encounters administrative and technical obstacles, as well as insufficient coordination among government institutions. Additionally, applying higher tax rates to taxpayers who fail to match their TIN with their NIN, without clear exemption mechanisms, has led to legal uncertainty and unfairness. Limited technological access and inadequate public understanding further exacerbate these issues. To address these challenges, a comprehensive evaluation, improved inter-agency coordination, enhanced public outreach, and transparent and clear exemption mechanisms are required. Consequently, this policy is expected to improve tax compliance while ensuring fairness and legal protection for all taxpayers.